Panel 8: Report on Recent Advances in Molecular and Cellular Biochemistry. (3rd April 2017) - Preciado, Diego; Granath, Anna; Lin, Jizhen; Val, Stéphanie; Kurabi, Arwa; Johnston, Nikki; Vijayasekaran, Shyan; Valdez, Tulio; Depireux, Didier; Hermansson, Ann
Abstract : Objectives: To update the medical literature on recent cellular and molecular advances in otitis media disease models with a principal focus on developments in the past 5 years. We also aim to explain recent translational advances in cellular and molecular biology that have influenced our understanding and management of otitis media. Data Sources: PubMed‐indexed peer‐reviewed articles. Review Methods: A comprehensive review of the literature was conducted with the term otitis media and the following search terms: molecular biology, cell biology, innate immunity, oxidative stress, mucins, molecular diagnostics . Included articles were published in the English language from January 1, 2010, to July 31, 2015. Implications for Practice: The molecular understanding of otitis media disease progression has rapidly advanced over the last 5 years. The roles of inflammation, mucins, and cell signaling mechanisms have been elucidated and defined. Advances in the field provide a plethora of opportunities for innovative molecular targeting in the development of novel therapeutic strategies for otitis media.